A Systematic Review of the Impact of Physical Exercise-Induced Increased Resting Cerebral Blood Flow on Cognitive Functions - Renke, Maria B.; Marcinkowska, Anna B.; Kujach, Sylwester; Winklewski, Paweł J. (Frontiers in Aging Neuroscience, 2022)
Brain perfusion declines with aging. Physical exercise represents a low-cost accessible form of intervention to increase cerebral blood flow; however, it remains unclear if exercise-induced amelioration of brain perfusion has any impact on cognition. We aimed to provide a state-of-the art review on this subject. A comprehensive search of the PubMed (MEDLINE) database was performed. On the basis of the inclusion and exclusion criteria, 14 studies were included in the analysis. Eleven of the studies conducted well-controlled exercise programs that lasted 12–19 weeks for 10–40 participants and two studies were conducted in much larger groups of subjects for more than 5 years, but the exercise loads were indirectly measured, and three of them were focused on acute exercise. Literature review does not show a direct link between exercise-induced augmentation of brain perfusion and better cognitive functioning. However, in none of the reviewed studies was such an association the primary study endpoint. Carefully designed clinical studies with focus on cognitive and perfusion variables are needed to provide a response to the question whether exercise-induced cerebral perfusion augmentation is of clinical importance.